Intraluminal Diverticular Duodenal Duplication With Recurrent Abdominal Pain: A Case Report - Chen, Jie; Xiong, Guo-zuo; Tan, Xiong; Wu, Fei; Luo, Dong-yang; Zou, Qing-qing; Deng, Zhihe; Bi, Guo-shan (Frontiers in Pediatrics, 2022)
Intraluminal tubular duodenal duplication is a rare congenital anomalies which may manifest as pancreatitis, gastrointestinal bleeding, abdominal pain, perforation and obstruction. We presented a case in which recurrent abdominal pain caused by a large hole-like structure in the duodenal bulb. An 11-year-old boy presented recurrent attacks of abdominal pain. An initial diagnosis was Intraluminal Diverticular Duodenal Duplication (IDDD) based on upper endoscopy examination and barium swallowing, which was confirmed by operative findings and histopathological signs. He underwent a subtotal excision and duodenal anastomosis. No serious complications occurred after treatment. The patient was followed up for 8 months, and his condition improved without symptoms.